Knowledge, attitude, and practice of cosmetic camouflage among dermatology residents - Jasleen Kaur Sandhu; Purva Pande; Mala Bhalla (Wolters Kluwer Medknow Publications, 2021)
Background: Cosmetic camouflage, used to temporarily normalize appearance, has been shown to improve quality of life in patients with visible disfiguring skin disorders. Its integration into the daily dermatology practice is affected by many hurdles, including dermatologists' perception about it. Knowledge gained during residency teaching likely affects future practices. Aims: This questionnaire-based survey study was planned to assess the knowledge, attitude, and practice about cosmetic camouflage among dermatology residents. Methods: Dermatology residents in four tertiary care hospitals were contacted for voluntary participation by anonymously filling out a questionnaire devised to assess the awareness of cosmetic camouflage among dermatology residents, various indications of recommendation, any inhibitions in recommending camouflage, problems faced while recommending, and so on. Results: Nearly all (30 of 31; 96.8%) of the dermatology residents in the survey were aware of cosmetic camouflage, but translation of this into practice was low as only about half (17 out of 31, 54.8%) had recommended it. Commonest indication known to the residents was vitiligo (27; 87.1%). The most frequent situation for recommendation felt by 20 (64.5%) respondents was in patients with significant disease related psychological morbidity. Most (18; 58.1%) respondents felt one or the other inhibition in recommending camouflage. The respondents felt that the commonest problem faced while recommending camouflage was availability of the camouflage products (21; 67.7%). Majority (13; 41.9%) thought it only had a "somewhat" role in dermatology. Conclusion: This study highlights the need to improve early education in residency regarding the option of cosmetic camouflage to address the cosmetic concerns of patients. Setting up of camouflage clinics in teaching hospitals may help in this.